2018
DOI: 10.1080/21691401.2018.1436553
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in synergistic chemotherapy and phototherapy by targeted drug delivery systems for cancer treatment

Abstract: Although it's pharmacological effect for cancer therapy, conventional chemotherapy has been compromised by a series of shortcomings such as limited stability, nonspecific tumour targeting ability and severe toxic side effects. To overcome these limitations, multifunctional targeted drug delivery systems for combinatorial therapeutics have been widely explored as novel cancer therapy strategies, showing encouraging results in many pre-clinical animal experiments. Among them, synergistic phototherapy and chemoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(42 citation statements)
references
References 55 publications
(126 reference statements)
1
41
0
Order By: Relevance
“…Hyperthermic conditions induced the efficient cell uptake of NPs with drug loading, stimulated drug release, and enhanced therapeutic outcomes. Moreover, chemo-photothermal combination therapy can augment cell membrane permeability [119,120]. Accordingly, many nanosystems for combined PTT and chemotherapy, including inorganic NPs [121], micelles [122], and polymeric NPs [123], have been developed.…”
Section: Photothermal Chemotherapymentioning
confidence: 99%
“…Hyperthermic conditions induced the efficient cell uptake of NPs with drug loading, stimulated drug release, and enhanced therapeutic outcomes. Moreover, chemo-photothermal combination therapy can augment cell membrane permeability [119,120]. Accordingly, many nanosystems for combined PTT and chemotherapy, including inorganic NPs [121], micelles [122], and polymeric NPs [123], have been developed.…”
Section: Photothermal Chemotherapymentioning
confidence: 99%
“…Cancer is a severe disease. Among the strategies combating cancer, chemotherapy is an important and highly effective treatment which has been promoted by nanotechnology [1]. Doxorubicin (DOX) is the first line chemotherapeutic agent used in many cancers [2].…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 However, due to its limited ability to distinguish human tumor cells from normal ones, chemotherapy drugs also affect normal cells while killing tumor cells. 3 To improve the therapeutic efficacy of antitumor drugs, it is essential to develop tumor-targeted drugs that can specifically accumulate in tumors and cause death of tumor cells without doing harm to normal ones. 3 5 Previous studies have found that one or more complement regulatory proteins (CD46, CD55, CD59) are highly expressed on various surface of tumor cells such as uterine serous carcinomas.…”
Section: Introductionmentioning
confidence: 99%
“… 3 To improve the therapeutic efficacy of antitumor drugs, it is essential to develop tumor-targeted drugs that can specifically accumulate in tumors and cause death of tumor cells without doing harm to normal ones. 3 5 Previous studies have found that one or more complement regulatory proteins (CD46, CD55, CD59) are highly expressed on various surface of tumor cells such as uterine serous carcinomas. 6 Studies showed that small interfering RNAs inhibiting CD55 and CD59 (but not CD46) expression in vitro could sensitize uterine serous carcinomas to complement-dependent cytotoxicity and antibodies-dependent cytotoxicity.…”
Section: Introductionmentioning
confidence: 99%